2017
DOI: 10.1080/23328940.2017.1303562
|View full text |Cite|
|
Sign up to set email alerts
|

Thermophysiological adaptations to passive mild heat acclimation

Abstract: Passive mild heat acclimation (PMHA) reflects realistic temperature challenges encountered in everyday life. Active heat acclimation, combining heat exposure and exercise, influences several important thermophysiological parameters; for example, it decreases core temperature and enhances heat exchange via the skin. However, it is unclear whether PMHA elicits comparable adaptations. Therefore, this study investigated the effect of PMHA on thermophysiological parameters. Participants were exposed to slightly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 50 publications
2
35
0
Order By: Relevance
“…Especially for metabolic rate, further studies need to make a clear distinction between behavioral effects on metabolic rate and physiological ones, given the ambiguous findings of field and laboratory studies, especially regarding heat adaptation. In addition, it has been shown previously that the process of physiological adaptation to both heat and cold is highly individual, even in relatively homogenous study populations [88,89,149]. It is likely that physiological adaptation differs even more, for example, between groups with different age and/or body composition.…”
Section: Demographic and Physiological Drivers Of Diversitymentioning
confidence: 98%
See 2 more Smart Citations
“…Especially for metabolic rate, further studies need to make a clear distinction between behavioral effects on metabolic rate and physiological ones, given the ambiguous findings of field and laboratory studies, especially regarding heat adaptation. In addition, it has been shown previously that the process of physiological adaptation to both heat and cold is highly individual, even in relatively homogenous study populations [88,89,149]. It is likely that physiological adaptation differs even more, for example, between groups with different age and/or body composition.…”
Section: Demographic and Physiological Drivers Of Diversitymentioning
confidence: 98%
“…Based on the results of a comprehensive literature review on the physiological aspects of heat adaptation by Taylor et al [90] and other physiological studies [89,139], it can be assumed that a decrease of metabolic rate in hot environments, which has earlier been suggested to be a physiological consequence of heat adaptation [140], is not due to physiological changes but is rather attributable to behavioral adjustments [90]. However, an enhanced metabolic response to cold exposure has consistently been reported as a result of cold adaptation [141].…”
Section: Physiological Adaptationmentioning
confidence: 99%
See 1 more Smart Citation
“…resting in hot-dry or hot-humid conditions) (Armstrong and Kenney 1993; Racinais et al 2016;Pallubinsky et al 2017), or by implementing thermal exposures, such as hot water immersion (HWI) (Zurawlew et al 2015;Ruddock et al 2016), or sauna post-exercise (Scoon et al 2007), the most common and potentially most potent HA methods require exercise-heat stress (Racinais et al 2015). A variety of HA protocols have been published ranging in durations of 4-20 days, utilising prolonged exposures (30-120-mins) typically in hot-dry or hot-humid conditions (~40°C, 40% relative humidity [RH]) (Tyler et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, exercising in heat (active HA strategy) is the most commonly accepted method to induce the following HA responses [10], all of which contribute to improved heat tolerance: (1) decrease in body core temperature; (2) reduction in heart rate; (3) lessened physiological strain index (PSI); (4) increase in sweat rate; (5) alleviated perceptual strain. Other studies advocated passive HA strategies, subjecting individuals to heat stress without any exercise mainly by immersion in hot water [11], entering a heat chamber [12], or sauna [13]. These studies suggested that active strategies are not necessary to induce HA as the main stimulus for heat adaptation is simply a repeated rise in body core temperature [14].…”
Section: Introductionmentioning
confidence: 99%